Field notes contributed by Paul Martsching for Story County, winter 1983-1984 - Martsching, Paulet al (1983)
Field notes were contributed by Paul Martsching for Story County, winter 1983-1984. Five species were listed: Gray Partridge, Red-headed Woodpecker, Golden-crowned Kinglet, Loggerhead Shrike, and Snow Bunting. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed